Biochemical properties of a Pseudomonas aminotransferase involved in caprolactam metabolism. (25th June 2019) - Palacio, Cyntia M.; Rozeboom, Henriëtte J.; Lanfranchi, Elisa; Meng, Qinglong; Otzen, Marleen; Janssen, Dick B.
Abstract : The biodegradation pathway of the nylon‐6 precursor caprolactam by a Pseudomonas bacterium includes deamination of 6‐aminohexanoate by an aminotransferase. The catalytic properties of this pyridoxal 5′‐phosphate fold type I enzyme were examined and structures were solved by protein crystallography. By comparing catalytic selectivities and structural properties of different aminotransferases, enzyme–substrate interactions relevant for the activity and selectivity of this novel aminotransferase were identified. Abstract : The biodegradation of the nylon‐6 precursor caprolactam by a strain of Pseudomonas jessenii proceeds via ATP‐dependent hydrolytic ring opening to 6‐aminohexanoate. This non‐natural ω‐amino acid is converted to 6‐oxohexanoic acid by an aminotransferase ( Pj AT) belonging to the fold type I pyridoxal 5′‐phosphate (PLP) enzymes. To understand the structural basis of 6‐aminohexanoatate conversion, we solved different crystal structures and determined the substrate scope with a range of aliphatic and aromatic amines. Comparison with the homologous aminotransferases from Chromobacterium violaceum ( Cv AT) and Vibrio fluvialis ( Vf AT) showed that the Pj AT enzyme has the lowest K M values (highest affinity) and highest specificity constant ( k cat / K M ) with the caprolactam degradation intermediates 6‐aminohexanoate and 6‐oxohexanoic acid, in accordance with its proposed in vivo function. Five distinct three‐dimensional structures of Pj AT were solved by protein crystallography. The structure of the aldimine intermediate formed from 6‐aminohexanoate and the PLP cofactor revealed the presence of a narrow hydrophobic substrate‐binding tunnel leading to the cofactor and covered by a flexible arginine, which explains the high activity and selectivity of the Pj AT with 6‐aminohexanoate. The results suggest that the degradation pathway for caprolactam has recruited an aminotransferase that is well adapted to 6‐aminohexanoate degradation. Database: The atomic coordinates and structure factors P. jessenii 6‐aminohexanoate aminotransferase have been deposited in the PDB as entries6G4B (E∙succinate complex), 6G4C (E∙phosphate complex), 6G4D (E∙PLP complex), 6G4E (E∙PLP‐6‐aminohexanoate intermediate), and6G4F (E∙PMP complex).